Comparison of Revision Risk Based on Timing of Knee Arthroscopy Prior to Total Knee Arthroplasty. (21st April 2021) - Gu, Alex; Fassihi, Safa C.; Wessel, Lauren E.; Kahlenberg, Cynthia; Ast, Michael P.; Sculco, Peter K.; Nunley, Ryan M.
Abstract : Background: Knee arthroscopy may be performed prior to total knee arthroplasty (TKA) in patients with symptomatic degenerative knee changes that do not yet warrant TKA. The purpose of this study was to determine whether the time interval between knee arthroscopy and subsequent primary TKA is associated with increased rates of revision and certain complications following TKA. Methods: Data from 2006 to 2017 were collected from a national insurance database. Patients who underwent knee arthroscopy within 1 year prior to primary TKA were identified and stratified into the following cohorts based on stratum-specific likelihood ratio (SSLR) analysis: 0 to 15, 16 to 35, 36 to 43, and 44 to 52 weeks from the time of knee arthroscopy to TKA. Univariate and multivariable analyses were conducted to determine the association between these specific time intervals and rates of revision surgery, periprosthetic joint infection (PJI), aseptic loosening, and manipulation under anesthesia. Results: In total, 130, 128 patients were included in this study; 6, 105 (4.7%) of those patients underwent knee arthroscopy within 1 year prior to TKA and 124, 023 (95.3%) underwent TKA without any prior knee surgery, including arthroscopy (the control group). Relative to the control group, the likelihood of undergoing revision surgery was significantly greater in patients who underwent knee arthroscopy ⩽15 weeks (odds ratio [OR]: 1.79; 95% confidence interval [CI]: 1.43 to 2.22; p < 0.001) or 16 to 35 weeks (OR: 1.20; 95% CI: 1.01 to 1.42; p = 0.035) prior to TKA. Patients were at significantly increased risk for PJI if knee arthroscopy was done ⩽35 weeks prior to TKA, and all 4 time groups that underwent knee arthroscopy within 1 year before TKA were at increased risk for manipulation under anesthesia. Conclusions: We found a time-dependent relationship between the timing of knee arthroscopy and complications following TKA, with the prevalence of revision surgery and PJI increasing as knee arthroscopy was performed closer to the time of TKA. This study suggests that an interval of at least 36 weeks should be maintained between the 2 procedures to minimize risks of PJI and revision surgery. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.